Improving Kinesthetic Intelligence through Animated Films in Children Aged 5-6 Years - Ruswanti, R; Fitriyah, Qonitah Faizatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to enhance the kinesthetic intelligence of 5-6-year-old children attending Aisyiyah Macanan Kindergarten in the Kebakkramat District through animated films tailored for their age group. Employing a descriptive qualitative approach, data were collected from 18 children in Group B through interviews, observations, and documentation. Data analysis was conducted using the triangulation technique. The findings indicate that teachers are well-versed in understanding children's kinesthetic intelligence, its characteristics, and the efficacy of using animated films for learning. Teachers have implemented varied learning media to prevent monotony and have ensured adequate facilities for presenting animated films. Children demonstrated proficiency in imitating movements depicted in the animated film "Nusa and Rara: Let's Exercise," contributing to gross motor skills such as hand-foot-eye coordination, body balance, strength, flexibility, and speed, all appropriate for their age group. Enhanced kinesthetic intelligence offers children increased opportunities for play, exploration, and social interaction with peers and their environment.